2017
DOI: 10.1007/s11284-017-1494-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in understanding mast seeding in relation to dynamics of carbon and nitrogen resources in temperate trees

Abstract: Mast seeding, the synchronous intermittent production of large seed crops in populations of perennial plants, is a widespread and widely studied phenomenon. Economy of scale has been demonstrated to provide the ultimate selection factor driving the evolution of masting, for example, in terms of the predatorsatiation and pollination-efficiency hypotheses; however, its physiological mechanism is still poorly understood. The resource budget (RB) model assumes that an individual plant requires more resources to fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 100 publications
4
42
0
2
Order By: Relevance
“…On the basis of the extended field network and survey of airborne pollen, we provide original and robust results supporting this 'resource-driven pollen limitation' hypothesis. Our results are in line with previous studies that pointed out the role of resource limitation in masting species, including oaks (Rapp et al 2013;Pesendorfer et al 2016), which suggest that flower and pollen production depend on the level of nitrogen reserve that fluctuates before and after a massive fruiting event (Sala et al 2012;Han et al 2014;Miyazaki et al 2014;Abe et al 2016), even if the limiting resource for pollen and fruit production remain controversial (Ichie et al 2013;Pearse et al 2016;Han & Kabeya 2017).…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the extended field network and survey of airborne pollen, we provide original and robust results supporting this 'resource-driven pollen limitation' hypothesis. Our results are in line with previous studies that pointed out the role of resource limitation in masting species, including oaks (Rapp et al 2013;Pesendorfer et al 2016), which suggest that flower and pollen production depend on the level of nitrogen reserve that fluctuates before and after a massive fruiting event (Sala et al 2012;Han et al 2014;Miyazaki et al 2014;Abe et al 2016), even if the limiting resource for pollen and fruit production remain controversial (Ichie et al 2013;Pearse et al 2016;Han & Kabeya 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Differing from Ichie et al, (), several studies showed that reproduction in masting species did not depend on stored carbon reserves (Hoch, Siegwolf, Keel, Körner, & Han, ; Igarashi, Shibata, Masaki, Tayasu, & Ichie, ). Reproduction in beech does not deplete stored carbohydrates, but it does change the amount of nitrogen stored (Han & Kabeya, ; see also Han, Kabeya, Iio, Inagaki, & Kakubari, ; Miyazaki et al, ), and masting in F . crenata is well explained by the interplay between stored nitrogen and climatic cues (Abe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen may have indirect effects on seed production through bio‐assimilation in Q. crispula , because in Quercus species, photosynthetic activity increases as the leaf nitrogen content increases (Takashima, Hikosaka, & Hirose, ). Our limited knowledge about carbohydrate–nitrogen interactions (Allen et al, ; Han & Kabeya, ) and the variation of carbon storage in relation to masting request further researches on the resource dynamics of masting.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with many studies indicating some level of resource limitation in masting species. Recent reviews (Crone and Rapp , Han and Kabeya ) analyzed resource depletion across many species and found several limiting variables (e.g., nutrients, structural carbohydrates) in some species, but not in others. These studies described the relative roles (important to insignificant) of plant nutrient availability and reserves for masting species, particularly phosphorus (Sala et al.…”
Section: Discussionmentioning
confidence: 99%